Teleology deprived of theology: a hayekian reading of Adam Smith - Arthen, Guilherme Veiga (2024)
The intellectual imbrication between Friedrich Hayek and the Scottish moral philosophers of the 18th century, especially Adam Smith, is well known. Hayek claims that they grasped the connection between spontaneous orders and evolution, in the sense that they were the pioneers in realising that they are \"twin ideas\" (Hayek, 1967a, 1973a, 1988). The conflation of these two theoretical traditions in Hayek\'s late social theory has been criticised by several authors (Barry, 1982; Vanberg, 1986; Petsoulas, 2013). Most of them associate this alleged misconception with Hayek\'s misapprehension of the theory of spontaneous orders evoked by those moral philosophers. In this sense, this work employs a Hayekian reading of Adam Smith and shows that the conflation is possible if we employ a teleological approach to the latter. Through the secular and teleological Hayekian lenses, Smith\'s social theory emerges as somewhat deterministic, since commercial society would already have been inscribed by nature in human beings, guiding their behaviour towards the conducts that are most conducive to the rise and maintenance of that social order.